Enhancing students satisfaction through campus climate - Zainal Abidin, Noor Saadah; Foo, Say Fooi; Uli, Jegak; Kasa, Zakaria (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study determines students' satisfaction in higher learning institutions (polytechnics) along the five dimensions identified from the literature. These include tangible factors (program, facilities, academic staff, .and support services) as well as an intangible factor which is campus climate. Differences among years and levels of studies were identified among various zones of the public higher learning institutions. This study aims to determine factors that strongly explain variance of students' satisfaction in such institutions. A total sample of 469 students was involved in this study. The data was collected through proportionate cluster sampling. All five factors were found to be linearly correlated with students' satisfaction. Campus climate was observed to be the strongest factor to explain variation of students' satisfaction. This study shows that beside tangible factors, the intangible aspects (campus climate) played an important role in explaining the variance of students' satisfaction. These findings imply that administrators in higher education institutions need to improve strategies aimed at achieving better students' satisfaction emphasizing tangible as well as intangible aspects to students.